Naturalistki przełomu wieków i prawdziwa natura ich pisarstwa: „Baby Buds” (1895) Ellis Ethelmer i „Skąd się wziął twój braciszek?” (1903, 1905) w przekładzie Róży Centnerszwerowej - Rajewska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
No further back than the late 19th century, equal access to education and science was a controversial issue, and to knowledge – even a taboo one. ‘A very difficult and delicate matter is treated with considerable skill, although many will think that it had better have been left alone’, read an 1896 review of Ellis Ethelmer’s “Baby Buds” from “The British Medical Journal”. This article focuses on different uses of natural science, especially botany, in children’s literature at the turn of the twentieth century in Great Britain and Poland, with the main case being a British botany primer for the youngest readers – actually a sex-education handbook, which triggered a serious and indeed heated debate among Polish literary critics, educators and parents, becoming an important element in the dispute over the shape of Polish education, girls’ education in particular.